KEARIFAN LOKAL DALAM HIKAYAT PANGERAN INDRA BANGSAWAN KARYA TRI SAPTARINI - Erlinda - Nofasari; Seget - Tartiyoso; Pratiwi Kurnia Sari (STKIP Budidaya Binjai, 2022)
The purpose of this study was to find out local wisdom in the saga of Prince Indra Bangsawan by Tri Saptarini. This type of research is a qualitative research with a qualitative descriptive method. The instrument in this study was the researcher himself who was assisted by the local wisdom analysis guideline of Sibarani theory. The results of this study indicate that the value of local wisdom in the saga of Prince Indra Bangsawan by Tri Saptarini is divided into two parts, namely the value of local wisdom of peace and the value of local wisdom of peace and prosperity. The value of local wisdom of peace in the saga of Prince Indra Bangsawan by Tri Saptarini consists of politeness, gratitude, positive thoughts, commitment, conflict resolution, and harmony. Meanwhile, the value of local wisdom of welfare in the saga of Prince Indra Bangsawan by Tri Saptarini consists of mutual cooperation, care for the environment, and health.